2011
DOI: 10.1002/jrs.2886
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in Pb8O5(XO4)2 (X = As and V) compounds

Abstract: Raman spectroscopy, polarized microscopy and thermal measurements were used to investigate the sequence of phase transition in the lead oxide salts Pb 8 O 5 (XO 4 ) 2 (where X = As and V). For Pb 8 O 5 (AsO 4 ) 2 , a second-order phase transition is observed at 500 K. For Pb 8 O 5 (VO 4 ) 2 , a second-order and a first-order structural phase transitions are observed at 425 and 525 K, respectively. The ferroelastic character of Pb 8 O 5 (VO 4 ) 2 is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Phases already observed in corroded bronzes were also reported (sulfates, chlorides and mixtures) . The references correspond to previous Raman studies where such phases have been already observed in bronze patina and/or to reference works on these phases . Table lists the phases identified for each item.…”
Section: Resultsmentioning
confidence: 79%
“…Phases already observed in corroded bronzes were also reported (sulfates, chlorides and mixtures) . The references correspond to previous Raman studies where such phases have been already observed in bronze patina and/or to reference works on these phases . Table lists the phases identified for each item.…”
Section: Resultsmentioning
confidence: 79%
“…Mishra and co‐workers reported a low‐temperature Raman study in NaNbO 3 in the temperature range 10–300 K to understand the low‐temperature antiferroelectric–ferroelectric phase transition . Oliveira and co‐workers studied phase transitions in the compounds Pb 8 O 5 (XO 4 ) 2 for X═As and V . Sharma et al .…”
Section: Solid‐state Studiesmentioning
confidence: 99%